The cost of globalization : dangers to the earth and its people - Kunnie, Julian (2015)
"This volume examines the many pitfalls of globalization from the perspective of impoverished and indigenous peoples, including the widening wealth gap, the struggle for restoration of dispossessed lands and cultural rights, global warming and ecological annihilation, and the experiences of women in underdeveloped regions who receive little benefit from their labor and are subject to violence"--
Includes bibliographical references (pages 283-359) and index.
Keywords: Anti-globalization movement; Externalities (Economics); Globalization -- Economic aspects; Globalization -- Social aspects; Poverty; Social justice; Print books